2011
DOI: 10.1071/hc11048
|View full text |Cite
|
Sign up to set email alerts
|

Clinical outcomes and patients’ perceptions of nurse-led healthy lifestyle clinics

Abstract: BACKGROUND AND CONTEXT: The Nurse-Led Healthy Lifestyle Clinics focussed on lifestyle issues for patients with known health inequalities. Much of the nursing was educative and preventative care. This evaluation assessed patient experiences and opinions, as well as clinical outcomes. ASSESSMENT OF PROBLEM: Information came from clinical outcome data for 2850 individuals and 424 patient satisfaction surveys. Results: Patients were aged 0–95 years (45% between 40 and 59 years); 60% Pakeha/European, 31.4% Maori, 4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
27
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(29 citation statements)
references
References 7 publications
2
27
0
Order By: Relevance
“…A number of studies have investigated patient satisfaction with nurse-led clinic interventions [15,16]. In their Australian paper, Mahomed et al [15] reported the development of a grounded theory of patients’ satisfaction from a larger study exploring a practice nurse-led model of chronic disease management.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A number of studies have investigated patient satisfaction with nurse-led clinic interventions [15,16]. In their Australian paper, Mahomed et al [15] reported the development of a grounded theory of patients’ satisfaction from a larger study exploring a practice nurse-led model of chronic disease management.…”
Section: Introductionmentioning
confidence: 99%
“…In New Zealand, Marshall et al [16] reported data from an 8-item survey on consultation satisfaction related to healthy lifestyle clinics. These items focussed broadly on satisfaction with the consultation, exploring factors such as adequacy of the consultation room and impact of the education provided on confidence and health.…”
Section: Introductionmentioning
confidence: 99%
“…In thirteen studies, primary care RNs carried out the intervention independently without the support of other staff/providers [ 45 , 46 , 49 , 51 , 53 55 , 57 – 60 , 62 , 63 ], and in 10 studies, they carried out the intervention interdependently, in collaboration with health care providers (e.g., physicians, clinical pharmacy specialists [CPS], dieticians) or members of the research team (e.g., trial nurse facilitator) [ 43 , 44 , 47 , 48 , 50 , 52 , 56 , 61 , 64 , 65 ]. Three of these 10 studies involved evaluating RNs at the general practice-level and therefore are assumed to be evaluating an interdependent role involving support of other health care providers [ 47 , 61 , 64 ].…”
Section: Resultsmentioning
confidence: 99%
“…Research has shown nurse-led clinics (NLCs) are effective in enhancing self-management of disease, 1,2 are an acceptable alternative to a general practitioner (GP) consultation, 3,4 provide equivalent care for minor conditions compared to GPs, 5 and are appreciated by patients for the extended time available for consults. 6 While NLCs have shown significant improvements in patient outcomes and perceptions of health care both overseas and in New Zealand, [7][8][9][10] there is limited information on nurses' experiences and opinions of their participation in NLCs. Phil-lips and colleagues 11 note, while not referring specifically to NLCs, the many nurses in their study who "expressed frustration at the limited clinical care they were able to provide in general practice".…”
Section: Introductionmentioning
confidence: 99%